Pengaruh Aromaterapi Lavender Terhadap Kualitas Tidur Lansia Di Klinik Harmonisasi Chi Medika Tahun 2025 - Tiary Novalia; Darmawansyah Darmawansyah; Erlina Panca Putri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
In Indonesia, approximately 40% to 50% of the population experiences sleep disorders, most of whom are elderly. These sleep disorders usually occur simultaneously with other conditions such as physical problems and mental illnesses (depression, anxiety disorders) that can lead to poor sleep quality. The purpose of this study is to determine the effect of lavender aromatherapy on sleep quality of elderly at Klinik Harmonisasi Chi Medika in 2025. The research method used was a true experiment with one experimental group or treatment group and one control group. The sampling technique used was purposive sampling with a total of 32 respondents. The results of the univariate pre-test analysis of sleep quality in the intervention group and control group showed that all respondents (100%) had poor sleep quality. The post-test of sleep quality in the intervention group showed that almost all respondents (87.5%) had good sleep quality. The control group showed that all respondents (100%) had poor sleep quality. The results of the bivariate analysis of the Wilcoxon test obtained p count in the intervention group (p=0.001). The control group (p=0.066). The Mann-Whitney test results on the post-test data showed that the mean rank of the intervention group was 8.69, while the control group was 24.31 with p = 0.000 (p < 0.05). Lavender aromatherapy has an effect on the sleep quality of elderly at Klinik Harmonisasi Chi Medika in 2025. The results of this study can be used as a reference for clinics or health care facilities to integrate lavender aromatherapy as a non-pharmacological complementary therapy in an effort to improve the sleep quality of elderly.